THE PARADIGMS AND THE SOCIAL RESPONSIBILITY OF THE COUNTER - Wong Torres, Zelma (2011)
New paradigms fruits of the constant changes, mechanistic insights to complex views are aspects that have enabled the evolution and development of the accounting profession, understood as a stage in which the task and function of a public accountant should be creative, innovative and strategic results for the growth of organizations through competitive management, and their task in the development of social responsibility. In today's society it is satisfied that the world is changing rapidly and today the market demands a process of transformation in all aspects is why in this article aims to highlight the importance and the need for a paradigm shift of the accounting profession, the latter being as innovative practitioner role so that it contributes to the effectiveness of socio-economic management.